Acquired von Willebrand syndrome is common in infants with systemic-to-pulmonary shunts: Retrospective case-series - Icheva, Vanya; Budde, Ulrich; Magunia, Harry; Jaschonek, Karl; Hinterleitner, Clemens; Neunhoeffer, Felix; Schlensak, Christian; Hofbeck, Michael; Wiegand, Gesa (Frontiers in Pediatrics, 2022)
Background: Although acquired von Willebrand syndrome (aVWS) has been described in congenital heart disease before, anatomical features leading to aVWS with characteristic reduction or loss of high molecular weight von Willebrand multimers (HMWM) are not well known. This study assesses the prevalence and effects of aVWS in infants with systemic-to-pulmonary shunts (SPS). Methods: This retrospective single-center study analyzes diagnostic data of infants with complex congenital heart defects requiring palliation with SPS. During the study period between 12/15-01/17 fifteen consecutive patients were eligible for analysis. Results of von Willebrand factor antigen (VWF:Ag), collagen binding activity (VWF:CB) and von Willebrand factor multimer analysis were included. Results: In all 15 patients with SPS an aVWS could be found. Blood samples were collected between 5-257 days after shunt implantation (median 64 days). None of the patients demonstrated increased bleeding in everyday life. However, 6 out of 15 patients (40%) showed postoperative bleeding complications after SPS implantation. Following shunt excision multimeric pattern normalized in 8 of 10 (80%) patients studied. Conclusions: This study shows that in patients undergoing SPS implantation aVWS might emerge. Pathogenesis can be explained by shear stress resulting from turbulent flow within the shunt. Knowledge of aVWS existence is important for the consideration of replacement therapy with von Willebrand factor containing products and antifibrinolytic treatment in bleeding situations. Implementation of methods for rapid aVWS detection is required to achieve differentiated hemostatic therapy and reduce the risk of complications caused by empiric replacement therapy.